The rape of Nanking : the forgotten Holocaust of World War II - Chang, Iris 1968-2004 (BasicBooks, 1997)
Details the massacre that took place in December 1937 when the Japanese army overthrew the ancient city of Nanking, China, and raped, tortured, and murdered over 300,000 civilians; examining the atrocity from the perspective of the Japanese soldiers, the Chinese civilians, and the Europeans and Americans who created a safety zone for survivors.